Measurement of Visual Eeg Signals Stimulated By Yellow Color Photons of Specific Wave Length At Different Intensities - Ramadhan, Shireen H. (Science Journal of University of Zakho, 2014)
Electroencephalography (EEG) is a diagnostic tool that records the electrical activity of the brain using numerous electrodes placed on various regions to the scalp, or in special cases on the cortex. The resulting traces are known as an electroencephalogram and represent so-called brainwaves.There are many types of stimulators (physical, chemical , and mechanical )that are affect the special senses sensitive areas in the brain which are collected as electrical signals. This research is concerned with photo stimulator (yellow color with frequency of ≈ 515 THz that is transmitted by visual nerve and the generated electrical signal waves are recorded by EEG. The sample of the research consists of 18 normal vision volunteers divided equally between males and females. All precautions of wave interference or artifacts that are due to physiological or external electrical source are taken into account and minimized into the ignored level.The results clearly showed that, the mean relative action potential amplitude recorded from O2 for males were the same in low and higher intensities ; when intensity was increased than that recorded from O1, and O2 channel for females also the same at low intensities then increased with increasing intensity than that recorded from O1.The fitting equation of the mean relative action potential amplitude versus the intensity of O1 and O2 channels for males are y = 0.053x2-3.161x + 47.23 with R2 = 0.969 and y = 0.044x2- 2.619x + 39.19 with R2 = 0.987, and for females are y = 0.046x2 – 2.693x + 39.60 with R2 = 0.894 and y = 0.043x2- 2.483x + 36.59 with R2 = 0.880 respectively.To compare the EEG electrical signals that are recorded from O1 and O2 channels for males and females, the mean relative action potential amplitudes are higher in males than in females for both channels. The deduced fitting curves for males O1 channel is y =0.046x2 – 2.693x + 39.60 with R2 = 0.894 and for females, O1 channel y =0.043x2 - 2.483x + 36.59 with R2 = 0.880 and that for male O2 channel is y = 0.044x2 – 2.619x + 39.19 with R2 = 0.987 and for female O2 channel y = 0.05x2 – 3.61x + 47.23 with R2 = 0.969.